Diurnal Effects of Periodic Litter Change on Egg Production and Physical Qualities in a Deep Litter System - Ndubuisi, E.C.; Iheukwumere, F.C.; Etusim, P.E. (International Journal of Poultry Science, 2008)
Five hundred and forty Lohmann hybrid point of lay birds aged 22 weeks were used to study the effect of periodic litter change on egg production and physical qualities. The birds were divided into 3 treatment groups consisting of 180 birds. Each treatment group was further replicated 3 times, made of 60 birds per replicate. Each treatment was allotted to three treatment periods of egg collection identified as T1 (morning 0700-1100 hrs). T2 (afternoon 1100-1400000 hrs) and T3 (evening 1400-1700 hrs) in a Completely Randomized Design (CRD). The birds were provided with water and feed ad-libitum. Litter was changed every 12 weeks and the experiment lasted for forty-eight weeks. The results of the climatic environmental conditions of the experimental site i.e. the ambient temperature, rectal temperature, relative humidity and wind velocity showed non significant difference (p>0.05) between T1 morning and T3 evening values but they differed significantly (p>0.05) from T2 afternoon values. The hen day egg production (61.15±0.87), hen housed egg production (59.04±0.91) and laying house mortality (4.69±0.43) for T1 morning were similar (p>0.05) to T3 evening hen day egg production (64.76±0.95), hen house egg production (61.41±0.73) and laying house mortality (3.91±0.42). Feed consumption, feed conversion and weight of the birds did not show any significant difference (p>0.05) between the treatment groups. The albumen weight, Haugh unit, egg length and width followed the same pattern as in the hen day egg production. The egg weight, yolk weight, shell weight and thickness in T1 morning, T2 afternoon and T3 evening did not differ (p>0.05) significantly between treatment groups. The pees-wees, cracked eggs and small-sized eggs were similar (p>0.05) in T1 morning and T3 evening period but significantly lower (p<0.05) than T2 afternoon values. The large sized and extra large eggs were similar in T1 and T3 but significantly (p<0.05) higher than T2 values. The results of this study show that litter change in a deep-litter system should be in the morning or evening must have finished egg laying for the day and when the ambient temperature must have fallen and is within the thermoneutrality zone between 12.8°C and 26°C.